Moda e rock: mudança na estética do produto atual - Souza, Lígia Amorim Rosa (2013)
In order to innovate in creation of wearable with band’s reference, will be inquiry through a bibliographical and documentary the objectives described like the history of the rock and its elements, as well as the behavior of its followers and the form of consumption produced by the product of the music. Respecting that the rock given rise by the black men and the poor people of the United States brought itself a historical luggage, full of movements cultural-partner, collecting admirers’ tribes all around the world. In this way, the rock is so much more than style of music, it’s a lifestyle, a form of demonstration, a representation of ideals, and finally a form of consumption. The symbology that it loads make as the followers don’t become contented just listen the music, but desire to express in them lifestyle through garment and adornments.